2021
DOI: 10.3390/ijms222111403
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Updated “Animal rDNA Loci Database” with an Emphasis on Its New Features

Abstract: We report on a major update to the animal rDNA loci database, which now contains cytogenetic information for 45S and 5S rDNA loci in more than 2600 and 1000 species, respectively. The data analyses show the following: (i) A high variability in 5S and 45S loci numbers, with both showing 50-fold or higher variability. However, karyotypes with an extremely high number of loci were rare, and medians generally converged to two 5S sites and two 45S rDNA sites per diploid genome. No relationship was observed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A relevant question is whether the rDNA loci tend to occur preferentially in one or another region on the chromosome. Big data analysis (the animal rDNA database is accessible online at www.animalrdnadatabase.com/, accessed on 1 June 2022) shows that rDNA may occur at nearly any chromosomal position, whereas there are significant trends in particular groups, including in some insects [64,65]. For example, differences in 45S rDNA positions seem to exist between two largest and most extensively studied "monocentric" insect groups, Coleoptera and Orthoptera: beetles show a preference for the distal position of 45S rDNA loci, whereas in orthopterans (at least in grasshoppers and crickets), a pericentromeric position is preferred, and terminal locations occur only in exceptional cases [64].…”
Section: Patterns Of 18s Rdna Localizationmentioning
confidence: 99%
“…A relevant question is whether the rDNA loci tend to occur preferentially in one or another region on the chromosome. Big data analysis (the animal rDNA database is accessible online at www.animalrdnadatabase.com/, accessed on 1 June 2022) shows that rDNA may occur at nearly any chromosomal position, whereas there are significant trends in particular groups, including in some insects [64,65]. For example, differences in 45S rDNA positions seem to exist between two largest and most extensively studied "monocentric" insect groups, Coleoptera and Orthoptera: beetles show a preference for the distal position of 45S rDNA loci, whereas in orthopterans (at least in grasshoppers and crickets), a pericentromeric position is preferred, and terminal locations occur only in exceptional cases [64].…”
Section: Patterns Of 18s Rdna Localizationmentioning
confidence: 99%
“…Ribosomal DNA mapping has been extensively used in many modern cytogenetic investigations (reviewed in [ 47 , 48 ]), constituting a valuable marker for cytotaxonomy [ 49 , 50 , 51 , 52 ]. In fish, copy number variation in rDNAs is frequently observed, since their gene regulation processes appear to be more relaxed in comparison with those of higher vertebrates [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of fish species present ribosomal DNA sites mapped on heteromorphic sex chromosomes [ 48 ], which can be explained by the presence of evolutionary breakpoint regions (EBRs), in several fish groups [ 50 , 54 , 55 , 56 ]. This feature is evident in karyomorph D, where 5S rDNA sequences can be identified in both X 1 and X 2 chromosomes and in the neo-Y chromosome [ 7 ] ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sochorová et al 2018Sochorová et al , 2021, and only rarely have multiple rDNA clusters been found (e.g., in some iguaniansAltmanová et al 2016;Rovatsos et al 2019b). Anguiform lizards, including Pseudopus apodus, exhibit hybridization signals on one pair of micro-or macrochromosomes (Heloderma is an exception with two macrochromosome pairs;Augstenová et al 2021).…”
mentioning
confidence: 99%